Layer-by-layer assembled polyelectrolyte-decorated graphene multilayer film for hydrogen gas barrier application - Liu, Hongyu; Bandyopadhyay, Parthasarathi; Kshetri, Tolendra; Kim, Nam Hoon; Ku, Bon-Cheol; Moon, Bongho; Lee, Joong Hee (ELSEVIER SCI LTD, 2017)
A facile approach for the fabrication of chemically-modified reduced graphene oxide (RGO) based multilayer films was developed for gas barrier applications. Polyethyleneimine (PEI) and poly(sodium 4-styrenesulfonate) (PSS) were utilized as surface modifiers to yield water-dispersible RGO with opposite charges. Altering the deposition pH of PEI-RGO layer resulted in different phase morphology and bonding of the multilayer films. PEI-RGO and PSS-RGO were assembled into multilayer films via a layer-by-layer (LbL) assembly method through electrostatic and hydrogen bonding interactions, respectively. The LBL assembly of polymer-decorated RGO based multilayer films were characterized by various characterization techniques. Hydrogen gas transmission rate (H(2)GTR) of the hydrogen bonding interaction based LbL film with 24 bilayers was 5.8 cc/m(2).d . atm; and H(2)GTR value was 46.2 cc/m(2).d . atm for the corresponding LbL film based on electrostatic interactions. Hydrogen bonding interaction based multilayer films exhibited very low H(2)GTR values compared to electrostatic interaction based multilayer and bare polyethylene terephthalate films. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: OXYGEN BARRIER; THIN-FILMS; MECHANICAL-PROPERTIES; OXIDE NANOCOMPOSITE; COMPOSITE FILM; TRANSPARENT; PROPERTY; DISPERSIONS; REDUCTION; HYBRIDS